A simple prognostic score predicts one‐year mortality of alert and calm emergency department patients: A prospective two‐center observational study. Issue 5 (3rd February 2020) - Nickel, Christian H.; Kellett, John; Nieves Ortega, Ricardo; Lyngholm, Le; Hanson, Stine; Cooksley, Tim; Bingisser, Roland; Brabrand, Mikkel
Abstract: Study Objective: To derive and validate a prognostic score to predict 1‐year mortality using vital signs, mobility and other variables that are readily available at the bedside at no additional cost. Methods: Post hoc analysis of two independent prospective observational studies in two emergency departments, one in Denmark and the other in Switzerland. Participants: Alert and calm emergency department patients. Measurements: The prediction of mortality from presentation to 365 days by vital signs, mobility and other variables that are readily available at the bedside at no additional cost. Results: One thousand six hundred and eighteen alert and calm patients were in the Danish cohort and 1331 in the Swiss cohort. Logistic regression identified age >68 years, abnormal vital signs, impaired mobility and the decision to admit as significant predictors of 365‐day mortality. A simple prognostic score awarded one point to each of these predictors. Less than two of these predictors were present in 45.6% of patients, and only 0.4% of these patients died within a year. If two or more of these predictors were present, 365‐day mortality increased exponentially. Conclusion: Age >68 years, the decision for hospital admission, any vital sign abnormality at presentation and impaired mobility at presentation are equally powerful predictors of 1‐year mortality in alert and calm emergency department patients. If validated by others these predictors could be used to discharge patients with confidence since nearly half of these patients had less than two predictors and none of them died within 30 days. However, when two or more predictors were present 365‐day mortality increased exponentially.